THE ROLE OF THE SUKABUMI CITY LABOR OFFICE IN INCREASING LABOR ABSORPTION IN SUKABUMI CITY - Rida Siti Shiyami Milenia; Tuah Nur; Dian Purwanti (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
One of the outstanding issues is the employment problem. Considering that a sizable portion of the labor force is still unemployed, there must be an equal distribution of employment throughout the workforce. The study's purposes were to identify the role of the Sukabumi City Labor Office in increasing labor absorption as well as its supporting and inhibiting factors in Sukabumi City. The theory used is the role theory of Jim Ife and Frank Toserioro, namely: 1) the role of facilitating; 2) the role of educating; 3) the role of representation; and 4) the technical role. A qualitative method using a descriptive approach was utilized. Then, the finding of this study was demonstrate that the Sukabumi City Labor Office contribution to increasing labor absorption in Sukabumi City is adequate but not ideal. Firstly, due to job searchers' abilities not meeting the company's requirements, the role of facilitating through job fair activities is still lacking, and there are still many candidates who have not been hired by the company. Secondly, providing an educational role through skill-training activities, the infrastructure and facilities for skill-training are inadequate due to financial restrictions. Thirdly, the Sukabumi City Labor Office only conducts apprenticeship activities with businesses that are in compliance with skills training, and there aren't many participants who are apprenticed. This limits the function of representation through apprenticeship activities. Besides that, there is supporting factor is the support from external parties who are involved in supporting and facilitating to increase labor absorption in Sukabumi City. The inhibiting factors are budget constraints, inadequate infrastructure, and a lack of quality Human Resources (HR).